Projeto de uma Casa de Férias em Ofir. Ato Experimental - Paulo Filipe Coutinho Lopes (2021)
The term vilegiatura has been known since old times. If, initially, the act of going on vacation was made for therapeutic reasons, now, is to create a break in everyday life. That is why, the intention of this essay was to study how architecture can provide this habit. In a first moment of this essay, it tried to understand the meaning of the word vilegiatura, as being associated with an old habit. In sequence, a brief understanding of what is a vacation home emerges - second home. Afterwards, by analyzing some resorts, the reasons by which they evolved were understood. After this understanding, the location where later will appear a proposal for vacation home, was analyzed. In a second moment, were studied several architectural references that helped the development of the proposal. That study reflects solutions that go towards what is intended to be done next, namely, that can support the implicit thinking in the proposal. Finally, a proposal for Ofir was made. Taking advantage from the reference cases studied above, some points of interest were applied in the project. Through this study and with the elaboration of the project, it was intended to respond effectively and assertively to the needs that the theme brings.